Students’ Perception towards the Use of Grammarly for Academic Writin: A Systematic Literature Review - Melda, Melda; Salam, Urai; Surmiyati, Surmiyati (Universitas Pahlawan Tuanku Tambusai, 2026)
Dependency on AI tools in academic has increases, Grammarly become one of the most frequent application to support students' writing processes. Most previous literature reviews have emphasized Grammarly's technical benefits in improving grammar and writing skills, along with pros and cons, while giving limited attention to students’ experiences and attitudes. This study addresses that deficiency by focus on analyzing students’ perceptions of Grammarly, both positive and negative. A systematic literature review collected relevant studies, and thematic analysis identified common themes. The results indicate that students generally view Grammarly positively due to its accessibility and usefulness in improving writing quality and skills. However, limitations such as the need for a stable internet connection, restricted features, and high subscription fees reduce its acceptance. This study offers valuable insights for educators and developers to enhance the educational relevance and effectiveness of AI writing tools.